Crisis Management at Cross-Roads - Challenges facing cross-border financial institutions at the EU level - Rym Ayadi; Morten Balling; Jaime Caruana; Johan Evenepoel; Ingimundur Fridriksson; Rosa Maria Lastra; Frank Lierman; Gregory Nguyen; Francesco Papadia; Peter Praet; Guy Quaden; Paul Tucker; et al. (SUERF - The European Money and Finance Forum, 2010)
On 16th November 2009, SUERF, CEPS and the Belgian Financial Forum coorganized a conference "Crisis management at cross-roads" in Brussels. All papers in the present volume are based on contributions at the conference and the SUERF Annual Lecture which followed the event.
Keywords: E5; E52; E53; E58; F31; F34; F36; G2; G21; G28; G3; G33; G34; G38; 330; Bank insolvency; capital adequacy; central banks; crisis management; crossborder banking; deposit guarantee system; deposit insurance; European Union; harmonisation; Iceland; interest rates; Lender of Last Resort; liquidity management; monetary policy; money markets; moral hazard; regulation; risk management; single market; supervision; too big to fail; volatility